تعقي السائل الأمنيوسي وعلاقته بالإنتان الجرثومي الباكر عند الوليد - ديوب عدنان; زاهر عزيز; صالح لمى (Latakia University Journal -Medical Sciences Series, 2019)
أجريت دراسة استقبالية لـ 65 حديث ولادة مع تعقي في السائل الأمنيوسي, حيث أجريت لهم تحاليل مخبرية و زروع جرثومية بعمر > 24 ساعة وأعيدت بعد 48 ساعة. وحسب الدراسة كان هناك عامل خطورة محتمل للتعقي في 36 مريضاً بنسبة 55,38%. وكان عامل الخطورة هذا توليدي في 20 مريضا بنسبة 55,56%, ووالدي في 11 مريضاً بنسبة 30,55%, بينما كان هناك 5 مرضى كان لديهم عامل مشترك والدي وتوليدي بنسبة 13,89%. ولم يكن هناك عامل متوقع ( للتألم أو الإنتان عند الوليد) في 29 حالة بنسبة 44,62% . كان الإنتان موجود في 10 مواليد بنسبة 9,1% لدى 9 مواليد منهم كان لديهم عامل خطورة محتمل للإنتان لدى الأم بنسبة 90% وفي حالة واحدة لم يكن هناك أي عامل محتمل لتطور الإنتان عند الوليد عدا التعقي بنسبة 10% . A prospective study was performed on 65 neonates with meconium-stained amniotic fluid; laboratorial and bacterial cultures were done in the first 24 hours, then repeated after 48 hours. According to this study, there was a possible cause for meconial liquid in 36 patients (55,38%). The risk factors were about the delivery process in 20 patients (55,56%), and maternal risk factors were (30,55%) in 11 patients; both causes were found in 5 patients (13,89%). There were no possible risk factors for stress or infection in 29 patients ( 44,62% ). Infection was found in 10 patients (9,1%). There was a possible risk factor of infection of the mother in 9 patients (90%), and one case showed no risk factors of neonatal infection, except for meconial liquid (10%).